Efectos jurídicos de la unión de hecho previo al nuevo estado civil de los cónyuges - Morán Olvera, Mayra Del Rocío (2015)
This thesis, whose theme is: "Legal effect of binding of fact prior to the new marital status of the spouses", consists of six chapters in which a summary of the topic under investigation unfolds. In the introduction, a conceptualization on the binding is done, its implication on society as a way to implement a family, on the critical, the reality on the de facto union focuses on marriage, the general objectives stated and specific, the hypothesis, independent and dependent variables and resources are detailed. In the theoretical framework, which consists of background research, rationale: Doctrine, Jurisprudence. Law and Comparative Law development the union, its evolution and legal recognition results from the object of study, referring to laws made especially the Constitution of the Republic and its lack of applicability to marriage. In the methodology, the methods used are determined, the techniques used in the field, the application of surveys to citizens of Canton Quevedo, Lawyer and interviews with such results tabulation, analysis and processing was performed data, reporting of research and hypothesis testing was developed, conclusions and recommendations formulated. The proposed legal reform to art. 222 of the Civil Code highlighting the importance of an adequate legal framework for the union.